ANALYSIS OF THE USE OF DIGITAL READING CORNERS AS A SOURCE OF STUDENT LEARNING AT SDN 16 MATARAM - Afifa, Istna Fiqriya; Khairunnisa, Izzati; Ilmi, Irda Hayyibi; Setiyani, Lilis; Rahmadhoan, Lulu (PROGRES PENDIDIKAN, 2025)
This study aims to describe the use of digital reading corners as a source of student learning at SDN 16 Mataram, responding to changes in the educational landscape due to technological advances. Using a qualitative descriptive approach, this study involved 15 3rd grade students as subjects, including 8 students and 7 female students. Data collection was carried out through interviews, direct observations, and field notes. The results of the study show that digital reading corners bring positive changes to students' reading habits, making them more diligent and enthusiastic about interactive digital books. It also encourages reading interest and improves overall literacy. However, there are obstacles such as limited access to digital devices and infrastructure, as well as a lack of interest in reading in conventional libraries. The proposed solutions include allocating school budgets for digital devices and the use of technology. This research provides insight into the potential of digital reading corners in improving the quality of learning and literacy, and emphasizes the importance of digital infrastructure investment to expand access to education and prepare students to face the digital era.